Explaining Education to Engineers: Feedback Control Theory as a Metaphor - Cheville, A.; Lindsay, Euan (IEEE, 2010)
One of the barriers for engaging engineering faculty in the scholarship of learning and teaching is thechallenge of learning a new vocabulary. Becoming fluent in engineering education requires the acquisitionof new concepts and ideas that are often expressed in unfamiliar terms. Feedback control is a technical fieldcommon to a range of engineering disciplines that can be used as a model to help bridge the conceptual gapbetween traditional engineering and engineering education. Many of the key elements of engineering education can be represented by the elements of a feedback control system, with their behaviour in a learning environment paralleling their behaviour in a process control context. The feedback control model can be used to explain: the importance of timely feedback to students, the significance of assessment and evaluation in the learning process, the impact of learning styles upon learning outcomes, and the need for student-centered teaching approaches. While both fields have complexities that cannot be captured by simple models, the basic ideas can be explained simply. Feedback control metaphors make the basics accessible to a wider audience of engineering faculty.